Accounting Perspectives on Tax Amnesty Policies in Indonesia: A Qualitative Literature Review and Case Study - Diah Nasrotul Afifa (Generate Digital Publishing, 2025)
Objective: This study aims to analyze accounting perspectives on the implementation of the 2016 Tax Amnesty (TA) in Indonesia, focusing on how financial reporting practices are carried out, particularly under PSAK 70.Research Design & Methods: This study uses a qualitative descriptive approach, combining a systematic literature review with a literature-based case study of corporate taxpayers participating in the 2016 Tax Amnesty program. Data were collected from academic publications, PSAK standards, tax regulations, and corporate financial reports. Findings: The study found that most entities chose PSAK 70 (prospective approach) rather than PSAK 25 (retrospective approach) to avoid the complexity of restatement. The main accounting issue lies in the conflict of equity presentation, where PSAK 70 requires the recording of asset-liability differences in Additional Paid-in Capital (APIC), while Law No. 11/2016 requires recognition in Retained Earnings. Conceptually, the APIC treatment provides greater transparency by separating non-operating profits from distributable profits.Implications & Recommendations: This finding emphasizes the need for regulatory harmonization between the IAI and the Directorate General of Taxes (DGT) to resolve inconsistencies in the presentation of equity and improve reporting consistency. Future studies should compare the 2016 Tax Amnesty with the Voluntary Disclosure Program (PPS) to assess the continuation of compliance behavior and evaluate the long-term impact of deemed costs on deferred tax liabilities in public companies. Contribution & Value Added: This study presents a comprehensive synthesis of PSAK 70 implementation, highlighting ethical and transparency dilemmas in equity reporting and offering policy insights to align tax laws and accounting regulations to ensure sustainable compliance and reliable financial disclosure.